2021
DOI: 10.3390/w13131771
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Virtual Water Trade Flow and Driving Factors in the European Union

Abstract: The inefficient application of water resources has become an urgent problem restricting the world’s sustainable development. Virtual Water Trade opens a new perspective on improving water resource utilization efficiency. Based on a multi-regional input–output model and the logarithmic mean Divisia index, the virtual water flows between 2000–2014 in 43 countries and regions have been evaluated, and the driving forces of changes in virtual water flows for the European Union were revealed. During the study period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Duarte et al applied SDA in order to determine the role of trade in the final net water balance in Spain, a semi-arid country with periodic severe water scarcity [ 18 ]. Using a multi-regional input–output model and a log-average divisor index, Fu et al revealed that economic and virtual water intensity effects are the most important drivers of virtual water flow changes in the EU [ 19 ]. However, there are a number of problems with existing correlation analysis methods applied to VWT drivers.…”
Section: Introductionmentioning
confidence: 99%
“…Duarte et al applied SDA in order to determine the role of trade in the final net water balance in Spain, a semi-arid country with periodic severe water scarcity [ 18 ]. Using a multi-regional input–output model and a log-average divisor index, Fu et al revealed that economic and virtual water intensity effects are the most important drivers of virtual water flow changes in the EU [ 19 ]. However, there are a number of problems with existing correlation analysis methods applied to VWT drivers.…”
Section: Introductionmentioning
confidence: 99%